Estimated Greenhouse Gas Emissions from PFAS Treatment of Maine Drinking Water - McAlexander, Benjamin; Apul, Onur; Olson, Mitchell; MacRae, Jean (Maine Policy Review, 2022)
State law requires the adoption of a maximum contaminant level (MCL) for PFAS contamination in drinking water by June 1, 2024. While discussion of mitigation options has included the degree of risk reduction and the cost of treatment, indirect environmental effects are missing from the conversation. Until other technologies are developed, water treatment in Maine will likely rely on the established, energy-intensive method of PFAS adsorption (binding) to granular activated carbon. We conducted an inventory of greenhouse gas emissions associated with water treatment using this treatment media to fill gaps in the discussion. We found that greenhouse gas emissions for water treatment to bring PFAS down to the current interim standard are substantial, raising the footprint of an average user by 6.7–18 percent. We use this information to discuss implications for policymaking.
Keywords: PFAS; greenhouse gas emissions; drinking water; activated carbon